Enhancing yield and nutrient use efficiency through coated gypsic fertilizer (Sparsh gold) in irrigated rice - Vakada, Manasa; Rajendran, Gobinath; Kuchi, Surekha (Journal of Cereal Research, 2019)
Rice farmers usually apply nitrogen, phosphorus and potassium at high rates to the crop. Whenever there is an imbalance between off take and input of nutrients, it may lead to a decline in soil fertility and increase incidence of deficiencies of certain plant nutrients especially sulphur and zinc (Sachdev and Sachdev, 2002). Sulphur and calcium are essential secondary nutrients for crop growth and development. Sulphur has an important role in chlorophyll production, protein synthesis and plant function and structure and also an important constituent of straw and plant stalks. Whereas, calcium is involved in development of a good root system and combines with pectin to form calcium pectate, which is an essential constituent of the cell-wall. It also promotes the activity of soil bacteria. So, there is a need to pay attention on sulphur and calcium nutrition of rice in intensively cropped areas and imbalanced fertilized soils. Though several chemical materials are available at present in the market, there is no specific compound exclusively for sulphur and calcium that has been reported to enhance the nutrient content and yield of rice through soil application. In view of this, Sparsh gold product was manufactured by using gypsum. Along with 16% Cereal Protein hydrolysate (CPH), potassium gluconate (C6H11O7 K) is also used (8%) in producing sparsh gold by coating gypsum. Sixteen different amino acids from vegetable source (maize-mostly) with plant growth substances and essential traces minerals and are coated on carrier gypsum. DOI: https://doi.org/10.25174/2249-4065/2019/95216